1964
DOI: 10.1042/bj0930611
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of cartilage matrix by an intracellular protease

Abstract: Papain has been shown by Thomas (1956) and Potter, McCluskey, Weissmann & Thomas (1960) to have a gross chondrolytic effect on rabbit ear cartilage in vitro and in vivo. It has been shown that the intravenous injection of the blood proenzyme plasminogen into rabbits during experimentally enhanced permeability conditions, which permit the diffusion and activation of the enzyme in carti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

1965
1965
1979
1979

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(54 citation statements)
references
References 28 publications
2
50
0
2
Order By: Relevance
“…To overcome these difficulties we developed a diffusion assay in which filters of controlled pore size were used; results obtained with this method confirmed the degree of inhibition by anti-(cathepsin D) sera. It is concluded that cathepsin D is the enzyme mainly responsible for the breakdown of proteoglycans during the autolysis of chicken and rabbit cartilage; a major role of cathepsin B proposed earlier (Ali, 1964) now seems to be excluded.…”
Section: Cartilage Autoly8i8mentioning
confidence: 81%
See 1 more Smart Citation
“…To overcome these difficulties we developed a diffusion assay in which filters of controlled pore size were used; results obtained with this method confirmed the degree of inhibition by anti-(cathepsin D) sera. It is concluded that cathepsin D is the enzyme mainly responsible for the breakdown of proteoglycans during the autolysis of chicken and rabbit cartilage; a major role of cathepsin B proposed earlier (Ali, 1964) now seems to be excluded.…”
Section: Cartilage Autoly8i8mentioning
confidence: 81%
“…Recent work has suggested that the lysosomal system plays a key role in the catabolism of the proteoglycans of cartilage (for reviews see Barrett, 1968;Dingle, 1969), and there is strong, though circumstantial, evidence that this process is mediated primarily by lysosomal cathepsin D. Other workers have proposed the involvement of hyaluronidase (Bollet, Handy & Sturgill, 1963;Weissman & Spilberg, 1968), cathepsinB (Ali, 1964;Ali, Evans, Stainthorpe & Lack, 1967) and fixylosidase (Fisher, Higham, Kent & Pritchard, 1966;Fisher, Whitehouse & Kent, 1967), whereas Woessner (1967) has added further weight to the indirect evidence in favour of the importance of cathepsin D. If the hypothesis that cathepsin D is the enzyme primarily responsible for the breakdown of cartilage matrix proves to be correct, it has important implications in the pathology of connective-tissue disease, particularly arthritis (Dingle, 1962(Dingle, , 1968Hamerman & Barland, 1966;PageThomas, 1969;Weissman & Spilberg, 1968). One way in which this hypothesis could be tested would be to inhibit the enzyme in a biological test system.…”
Section: Strangew6ay8mentioning
confidence: 99%
“…4 per cent, a hexuronate content of 23. 8 per cent, and a protein content of 16.0 per cent calculated as percentage of dry weight determined by methods described by Pal et al12 In these experiments the PP-L was dissolved in appropriate buffers to a final concentration of 5 mg./ml. Rabbit peritoneal polymorphonuclear leucocytes, obtained by the method of Cohn and Hirschle were resuspended in isotonic NaCl solutions and disrupted by six cycles of freezing and thawing.…”
mentioning
confidence: 99%
“…Lippiello 1969). Alternatively, trauma to the chondrocytes releases proteolytic enzymes capable of degrading proteoglycans (Ali 1964, Woessner & Sapolsky 1975. Whichever process is responsible, there is definite histochemical evidence in the present experiment, i.e., the localized loss of safranin 0 uptake (Rosenberg 1971), that the concentration of glycosaminoglycans is diminished in the superficial zone of the articular cartilage of the overstressed area.…”
Section: Discussionmentioning
confidence: 99%